2017
DOI: 10.6065/apem.2017.22.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transient congenital hypothyroidism in children with eutopic thyroid gland

Abstract: PurposeCongenital hypothyroidism (CH) is the most common cause of preventable mental retardation. Recently, the detection of CH cases with eutopic thyroid gland has increased due to neonatal screening programs. In this study, we aimed to identify and evaluate predictive factors that could distinguish between permanent and transient CH in patients with eutopic thyroid gland.MethodsWe retrospectively reviewed 100 children diagnosed with CH and with eutopic thyroid gland. All subjects were treated with levothyrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 15 publications
8
34
2
8
Order By: Relevance
“…18 The incidence of permanent CHT in cases with a normal or hyperplastic gland in our study was 52.2%. This was higher than the rate of 35% that was observed in a recent Korean study 19 but lower than rates observed in other studies worldwide in which the authors reported that 60% to 64% of patients with CHT had permanent hypothyroidism at the 3-year follow-up. 20 -22 Published studies of temporal changes in CHT incidence rates reveal conflicting results.…”
Section: Discussioncontrasting
confidence: 73%
“…18 The incidence of permanent CHT in cases with a normal or hyperplastic gland in our study was 52.2%. This was higher than the rate of 35% that was observed in a recent Korean study 19 but lower than rates observed in other studies worldwide in which the authors reported that 60% to 64% of patients with CHT had permanent hypothyroidism at the 3-year follow-up. 20 -22 Published studies of temporal changes in CHT incidence rates reveal conflicting results.…”
Section: Discussioncontrasting
confidence: 73%
“…This research assessed CH using cord blood TSH because this technique has become the gold standard in many parts of the world, as reported by the American Academy of Pediatrics, and because TSH screening is more specific in the diagnosis of CH [7,9]. It is known that in civilized countries, neonatal screening is widely adopted, which enables early diagnosis of CH in neonates, so severe mental retardation due to CH is very rare in these countries [11]. On the other hand, we adopted this technique and not another one because hypothyroidism assessed by capillary TSH needs to be confirmed by venous TSH [1].…”
Section: Discussionmentioning
confidence: 99%
“…Primary screening of thyroid-stimulating hormone (TSH) levels has become standard in many parts of the world [7]. If the diagnosis of hypothyroidism is made a few weeks after birth and the treatment starts early, neurodevelopmental outcomes are generally normal [10,11]. The first screening program for CH was conducted in North America in 1972 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Also, transient hypothyroidism tends to respond to a lower dosage of L-T4 than CH. 7,15,24,25 Kashiwagura et al 26 successfully administered a suppository preparation of L-T4 in patients with hypothyroidism who could not take thyroid hormones by mouth. Because our patient was incapable of receiving oral administration of L-T4 and because intravenous and suppository preparations of L-T4 were not available at our hospital, we decided to empirically administer a rectal diluted solution of L-T4.…”
Section: Discussionmentioning
confidence: 99%
“…2 -6 The prevalence goes up to 65% if we consider patients with a eutopic gland. 7 Premature (<37 weeks' gestation) infants and those with very low birth weight (BW) (<1500 g) are especially at risk for hypothyroidism because of iodine deficiency. 8,9 Early diagnosis and treatment are needed to avoid complications.…”
mentioning
confidence: 99%